The Role of Greetings And Introductios in Developing Communicative Conpetence Among Young Learners - Purba, Citra Novita; Ginting, Gracetisya Audry Aurellia; Nazlah, Amalia; Br. Siregar, Tiarnita Maria Sarjani (EDU SOCIETY: JURNAL PENDIDIKAN, ILMU SOSIAL DAN PENGABDIAN KEPADA MASYARAKAT, 2025)
Greetings and introductions are fundamental communicative competencies that play an essential role in early English language learning, particularly at the elementary school level. This article examines the concepts, functions, and importance of greetings and introductions, as well as effective strategies for teaching these skills to young learners. Using a literature review approach, this study analyzes theoretical and empirical sources related to basic English communication and young learner pedagogy. The findings show that teaching greetings and introductions significantly contributes to students’ confidence, social interaction skills, and foundational speaking abilities. Effective strategies such as role play, language games, audiovisual media, and the Communicative Language Teaching (CLT) approach can enhance students’ participation and comprehension.